A 2000-year history of disturbance and recovery at a sacred site in Peru's northeastern cloud forest. (November 2017) - Matthews-Bird, Frazer; Valencia, Bryan G; Church, Warren; Peterson, Larry C; Bush, Mark
The last 2000 years in the tropical Andes was both a time of major pre-Hispanic and Hispanic period cultural developments, and increased climate variability. From c . AD 1000, Andean societies underwent significant transformation and many sites previously integrated under imperial Wari hegemony were abandoned. It has been argued that this sociopolitical reorganization was, in part, a response to the heightened climate variability of the late-Holocene. Here, we present a 2000-year diatom record from the cloud forest setting of Laguna de los Condores, in the Peruvian Andes. Cliff tombs overlooking the lake and a nearby abandoned village form one of the most important archaeological complexes in the Peruvian Chachapoyas region. The presence of diatoms that indicate high productivity (e.g. Planothidium frequentissimum and Amphora pediculus ) from as early as 2000 cal. yr BP suggest the lake was impacted by human activity predating the construction of monumental architecture and the regional Chachapoya cultural identity. The diatom fauna is consistent with sediment geochemical evidence that suggests high terrigenous input during the same period that would indicate that the surrounding catchment was disturbed. After c . AD 900 (1050 cal. yr BP), the diatom assemblage becomes dominated by species more indicative of a less productive system, coincident with a declining sedimentation rate, and a decrease in total biogenic silica: conditions that persist to modern times. The transition from a lake with high productivity receiving high erosional input to a less productive more stable system is contemporaneous with an increase in archaeologically documented mortuary and settlement activity. This period of declining terrigenous input is at odds with regional climate, which suggests a wetter than average period. Our data suggest the occupants of Laguna de los Condores changed their land use practices, as the region became wetter, and, in so doing, reduced erosion around the lake.